Two new Hyalella (Amphipoda: Hyalellidae) from the Puna and High Andean ecoregions of South America - Isa Miranda, Agueda Veronica (2025)
This paper presents two species of Hyalella, H. inca sp.n. and H. oscari sp.n., discovered in the Puna and High Andes regions of Argentina, South America. From these findings, the total of Hyalella species in Argentina is now 16. The newly discovered species are comprehensively described, illustrated, sequenced, and compared to morphologically similar and phylogenetically related species. New cytochrome c oxidase I (COI) sequence data were obtained for both new species, revealing their phylogenetic relationships, particularly to species from Lake Titicaca. These findings offer new insights into the Hyalella lineages in the High Andes and Puna ecoregions of South America, emphasizing the need for a detailed molecular genetic study using various genetic markers to explore them more deeply.